2014
DOI: 10.1093/nar/gku206
|View full text |Cite
|
Sign up to set email alerts
|

Functional redundancy between the transcriptional activation domains of E2A is mediated by binding to the KIX domain of CBP/p300

Abstract: The E-protein transcription factors play essential roles in lymphopoiesis, with E12 and E47 (hereafter called E2A) being particularly important in B cell specification and maturation. The E2A gene is also involved in a chromosomal translocation that results in the leukemogenic oncoprotein E2A-PBX1. The two activation domains of E2A, AD1 and AD2, display redundant, independent, and cooperative functions in a cell-dependent manner. AD1 of E2A functions by binding the transcriptional co-activator CBP/p300; this i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 70 publications
1
31
0
2
Order By: Relevance
“…We have assessed the relative severity of the disorder of all family members using the clinical score proposed for the use of subcutaneous immunoglobulin/intravenous immunoglobulin, 21 which is based on the frequency and severity of immune sequelae of CVID (Table 1). Application of the Ameratunga et al 2, 19 diagnostic criteria for CVID concluded that the proband (II.2) and her son (III.1) were phenotypically distinct from other family members (clinical score >10) and the highest clinical score was assigned to the proband.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have assessed the relative severity of the disorder of all family members using the clinical score proposed for the use of subcutaneous immunoglobulin/intravenous immunoglobulin, 21 which is based on the frequency and severity of immune sequelae of CVID (Table 1). Application of the Ameratunga et al 2, 19 diagnostic criteria for CVID concluded that the proband (II.2) and her son (III.1) were phenotypically distinct from other family members (clinical score >10) and the highest clinical score was assigned to the proband.…”
Section: Resultsmentioning
confidence: 99%
“…Nine variants affecting genes with known roles in the immune system were genotyped in the entire kindred (Supplementary Table 3). Of these, only a de novo frameshift nonsense mutation in TCF3 encoding the E2A transcription factors E12 and E47 21 segregated with the two severely symptomatic family members, II.2 and III.1 (Figures 1a and b) in the wider family. TCF3 plays a critical role in early B-cell development.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon further investigation we determined that assembly of the MYB TAD with P300/CBP is critical for Gal4-MYB-mediated activation within Polycomb chromatin. Celastrol inhibits the interaction of p300/CBP with MYB by binding to the CBP KIX domain (74)(75)(76)(77) , and completely reduces Gal4-MYB activity. In contrast, the Gal4-P65 and Gal4-VP64 fusions showed robust activation of PRC-silenced luciferase in the presence of celastrol ( Figure 5B).…”
Section: Discussionmentioning
confidence: 99%
“…Both E2A and E2A-Pbx1 recruit p300/CBP via direct and cooperative binding via AD1 and AD2 (Bayly et al, 2004; Denis et al, 2014). AD1 in this context appears to be especially important given that a single mutation of a conserved Leu within PCET, which disrupts p300 interaction, also disrupts the leukemogenic function of E2A-Pbx1 (Bayly et al, 2006).…”
Section: Eto/e-protein Axis In Leukemogenesis and Hematopoiesismentioning
confidence: 99%